Analisis Tradisi Seren Taun Sebagai Sarana Pelestarian Kebudayaan Sunda di Era Globalisasi - Aradea Ferescky; Desy Safitri; Sujarwo, Sujarwo (FKIP, Universitas Palangka Raya, 2024)
In the midst of the practical and modern era of globalization, the seren taun tradition is still routinely carried out by the Sundanese people, especially those in the provinces of West Java and Banten. The essence of the seren taun tradition is an expression of gratitude for the harvest obtained and the hope that the harvest will be abundant again in the following year. In the seren taun tradition there are many values ​​and cultural elements contained and must continue to be preserved so that they are not lost as a result of globalization. The aim of this research is to analyze the implementation of the seren taun tradition in efforts to preserve Sundanese culture in the current era of globalization. This research method uses the Systematic Literature Review (SLR) method, with the stages of collecting, identifying, analyzing and evaluating the results of previous research on the seren taun tradition in various regions in West Java and Banten. The findings from this research show that the seren taun tradition can be used as a means of preserving Sundanese culture, because there are many elements of Sundanese culture contained in this series of traditions, starting from dance, musical instruments, literature, traditional clothing, entertainment, to noble values